Surging blue economy, increasing conflict risks and mitigation strategies - Sumaila, U. Rashid; Villasante, Sebastian (Frontiers in Marine Science, 2025)
The Blue Economy is raising optimism worldwide but the human expansion into, and the overcrowding of, the Ocean threatens increasing conflict between sectors, marine life, and the people who depend on it. Here, we highlight the potential conflicts that may arise between and within blue economy sectors, and provide recommendations on how to minimize such conflicts.